Anoxic growth of Ensifer meliloti 1021 by N2O-reduction, a potential mitigation strategy - Bueno, Emilio; Mania, Daniel; Frostegard, Ǻsa; Bedmar, Eulogio J.; Bakken, Lars R.; Delgado, Maria J. (Frontiers in Microbiology, 2015)
Denitrification in agricultural soils is a major source of N2O. Legume crops enhance N2O emission by providing N-rich residues, thereby stimulating denitrification, both by free-living denitrifying bacteria and by the symbiont (rhizobium) within the nodules. However, there are limited data concerning N2O production and consumption by endosymbiotic bacteria associated with legume crops. It has been reported that the alfalfa endosymbiont Ensifer meliloti strain 1021, despite possessing and expressing the complete set of denitrification enzymes, is unable to grow via nitrate respiration under anoxic conditions. In the present study, we have demonstrated by using a robotized incubation system that this bacterium is able to grow through anaerobic respiration of N2O to N2. N2O reductase (N2OR) activity was not dependent on the presence of nitrogen oxyanions or NO, thus the expression could be induced by oxygen depletion alone. When incubated at pH 6, E. meliloti was unable to reduce N2O, corroborating previous observations found in both, extracted soil bacteria and Paracoccus denitrificans pure cultures, where expression of functional N2O reductase is difficult at low pH. Furthermore, the presence in the medium of highly reduced C-substrates, such as butyrate, negatively affected N2OR activity. The emission of N2O from soils can be lowered if legumes plants are inoculated with rhizobial strains overexpressing N2O reductase. This study demonstrates that strains like E. meliloti 1021, which do not produce N2O but are able to reduce the N2O emitted by other organisms, could act as even better N2O sinks.